Idiopathic Intracranial Hypertension: An Unusual Cause of Headache in a Patient With Sickle Cell Disease - Toby Terwilliger MD; Mary Ann Kirkconnell Hall MPH; Eric Galante MD (SAGE Publishing, 2022)
Idiopathic intracranial hypertension (IIH) is a rare cause of headache and visual disturbance with no known association with sickle cell disease (SCD). We present a patient with SCD with gradual onset of a severe headache and visual changes. Brain magnetic resonance imaging, angiography, and venography were nondiagnostic. Lumbar puncture established a diagnosis of IIH, and the patient had rapid improvement with large-volume lumbar puncture and acetazolamide. To our knowledge, this is the first case of IIH in a nonobese adult with SCD taking hydroxyurea, suggesting an association between SCD or hydroxyurea use and IIH. Furthermore, her clinical course demonstrates the complexities of treating IIH in patients with SCD.